Power of computed-tomography-defined sarcopenia for prediction of morbidity after pancreaticoduodenectomy - Linder, Nicolas (BMC Med Imaging, 2019)
BACKGROUND: The goal of our study was to evaluate the current approach in prediction of postoperative major complications after pancreaticoduodenectomy (PD), especially symptomatic pancreatic fistula (POPF), using parameters derived from computed tomography (CT). METHODS: Patients after PD were prospectively collected in a database of the local department of surgery and all patients with CT scans available were assessed in this study. CT parameters were measured at the level of the intervertebral disc L3/L4 and consisted of the areas of the visceral adipose tissue (A(VAT)), the diameters of the pancreatic parenchyma (DPP) and the pancreatic duct (DPD), the areas of ventral abdominal wall muscle (A(MVEN)), psoas muscle (A(MPSO)), paraspinal muscle (A(MSPI)), total muscle (A(MTOT)), as well as the mean muscle attenuation (MA) and skeletal muscle index (SMI). Mann-Whitney-U Test for two independent samples and binary logistic regression were used for statistical analysis. RESULTS: One hundred thirty-nine patients (55 females, 84 males) were included. DPD was 2.9 mm (Range 0.7–10.7) on median and more narrow in patients with complications equal to or greater stadium IIIb (p < 0.04) and severe POPF (p < 0.01). DPP median value was 17 (6.9–37.9) mm and there was no significant difference regarding major complications or POPF. A(VAT) showed a median value of 127.5 (14.5–473.0) cm(2) and was significantly larger in patients with POPF (p < 0.01), but not in cases of major complications (p < 0.06). A(MPSO), A(MSPI), A(MVEN) and A(MTOT) showed no significant differences between major complications and POPF. MA was both lower in groups with major complications (p < 0.01) and POPF (p < 0.01). SMI failed to differentiate between patients with or without major complications or POPF. CONCLUSION: Besides the known factors visceral obesity and narrowness of the pancreatic duct, the mean muscle attenuation can easily be examined on routine preoperative CT scans and seems to be promising parameter to predict postoperative complications and POPF.